Editorial Team - TTHR (The Toro Historical Review, 2024)
The Toro Historical Review Volume 15, Issue 1 Editorial and Production Team Efrain Contreras Alexander Gonzalez Michael Gonzalez Shaleyah Haywood Ava Kostka Issac Rivera Dr. Joshua J. Jeffers, faculty mentor